2016
DOI: 10.1002/art.39573
|View full text |Cite
|
Sign up to set email alerts
|

Group for Research and Assessment of Psoriasis and Psoriatic Arthritis 2015 Treatment Recommendations for Psoriatic Arthritis

Abstract: Objective To update the 2009 Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) treatment recommendations for the spectrum of manifestations affecting patients with psoriatic arthritis (PsA). Methods GRAPPA rheumatologists, dermatologists, and PsA patients drafted overarching principles for the management of PsA, based on consensus achieved at face-to-face meetings and via online surveys. We conducted literature reviews regarding treatment for the key domains of PsA (arthritis, spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
772
0
74

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 814 publications
(862 citation statements)
references
References 35 publications
16
772
0
74
Order By: Relevance
“…The clinical manifestations of PsA include arthritis, enthesitis, dactylitis, spondylitis, psoriasis, and nail disease, with approximately 50% of patients also experiencing erosive joint damage within the first 2 years [10]. Thus, therapeutic principles should comprise management of disease in each tissue compartment, with the ultimate goal of impeding disease progression and maximizing function over time [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical manifestations of PsA include arthritis, enthesitis, dactylitis, spondylitis, psoriasis, and nail disease, with approximately 50% of patients also experiencing erosive joint damage within the first 2 years [10]. Thus, therapeutic principles should comprise management of disease in each tissue compartment, with the ultimate goal of impeding disease progression and maximizing function over time [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, clinical experience suggests that these agents are effective at reducing inflammation and treating some symptoms and signs and they remain the recommended first-line treatment option for patients with active PsA across several current international guidelines [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Expert opinion is that intraarticular steroid injections may be used in persistent mono-or oligoarthritis. 19 Observational evidence showed that 41% of joints improved at 3 months following use of corticosteroids, although 33% of these relapsed subsequently. 20 Oral steroids are not recommended, in part because of possible skin 'rebound' when they are withdrawn.…”
Section: Pharmaceutical Therapymentioning
confidence: 99%
“…19 Both of these recommendations are evidence-based and both broadly suggest a similar 'step up' approach to therapy. This approach uses therapies sequentially starting with simple therapies such as non-steroidal antiinflammatory drugs for pain or topical therapies for psoriasis, followed by single disease modifying drugs (DMARDs), then combinations of standard DMARDs, and finally biologic drugs if patients fail to respond to the previous treatment.…”
Section: Pharmaceutical Therapymentioning
confidence: 99%
“…In PsA clinical trials, spine involvement and spine response to treatment is not usually assessed because patients with spondylitis are in the minority, its presentation can be quite variable, and accurate spondylitis diagnosis and assessment of response would require extensive and expensive magnetic resonance imaging (MRI), as well as clinical assessment. Thus, to establish treatment recommendations for PsA spondylitis, international groups such as the Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) use data from ankylosing spondylitis (AS) trials as a surrogate for spondylitis response in PsA 20 . In AS studies, none of the traditional oral disease-modifying antirheumatic drugs (DMARD), including MTX, have demonstrated efficacy in the spinal manifestations of the disease.…”
mentioning
confidence: 99%